2005
DOI: 10.1159/000083509
|View full text |Cite
|
Sign up to set email alerts
|

The Psoriasis Area and Severity Index Is the Adequate Criterion to Define Severity in Chronic Plaque-Type Psoriasis

Abstract: Background: Chronic plaque-type psoriasis is a major dermatosis, but a significant question is still unanswered: What defines severity in chronic plaque-type psoriasis? While objective assessments like the Psoriasis Area and Severity Index (PASI) have frequently been used in clinical trials, quality of life (QOL) questionnaires are currently becoming more and more popular. Objective: This article summarizes the most important objective and subjective measurements of severity in psoriasis. For every dermatologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
290
0
13

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 394 publications
(313 citation statements)
references
References 58 publications
2
290
0
13
Order By: Relevance
“…The ointment was applied once a day, for two hours. The intensity of psoriasis before and after two weeks of treatment was assessed using the PASI (Psoriasis Area and Severity Index) score according to Fredriksson and Pettersson [17], which is still widely use to estimate severity of the disease [18,19]. The erythema, infiltration and desquamation were separately estimated on the head, trunk, upper and lower limbs.…”
Section: Methodsmentioning
confidence: 99%
“…The ointment was applied once a day, for two hours. The intensity of psoriasis before and after two weeks of treatment was assessed using the PASI (Psoriasis Area and Severity Index) score according to Fredriksson and Pettersson [17], which is still widely use to estimate severity of the disease [18,19]. The erythema, infiltration and desquamation were separately estimated on the head, trunk, upper and lower limbs.…”
Section: Methodsmentioning
confidence: 99%
“…Physical status was measured using the Health Assessment Questionnaire (HAQ) disability index [24]. Psoriasis severity was rated according to the Psoriasis area severity index (PASI) in PsA patients [25]. PASI combines the assessment of the severity of lesions and the affected area into a single score in the range from 0 (no disease) to 72 (maximal severity).…”
Section: Clinical Variablesmentioning
confidence: 99%
“…Severity of psoriasis is evaluated by the Psoriasis Area and Severity Index (PASI, 3 Ref. 13), which in case of treatment with Alefacept, improves rather late during successful therapy. In a recent study, 55% of Alefacept-treated patients showed a remission of Ն50% of the psoriasis symptoms.…”
mentioning
confidence: 99%